Management of Broken Endodontic Instruments in the Apical Third of Right Central Incisor Using the Braid Technique - Putu Mariati Kaman Dewi (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: Complication that can happened during root canal preparation is separation of endodontic instruments during cleaning and shaping Separated instruments can influence the cleaning of the root canal and the obturation of the root canal system becomes incomplete. Therefore, broken instruments in the root canal should be removed so that root canal cleaning can be carried out optimally. Retrieval of broken instruments in the root canal must be attempted manually or by using special instruments. This article discusses the procedure for removing broken endodontic instruments in the apical third of a tooth using the braid technique. Case report and management: a 34-year-old male patient came with complaints of a broken instrument during root canal treatment. Currently the patient's are not in pain. The therapy was carried out by taking a broken lentulo instrument using a braiding technique. After the broken instrument was removed, calcium hydroxide was applied to the root canal as intracanal medicament. A week later the root canal was obturated using the lateral condensation technique. The patient was then instructed to return to the general dentist who had previously treated him for restoration of the tooth that had undergone root canal treatment. Conclusion : Fracture of instruments in the root canal is influenced by the operator's ability, the instrumentation process and the anatomy and morphology of the root canal. One simple technique that can be used by operators to increase the success of retrieving broken instruments is the Braiding technique so that hermetic obturation can be achieved